The long hedge : preserving organisational value through climate change adaptation - West, Jason (Responsible investment series., 2014)
Part of the Greenleaf Publishing Responsible Investment Series. Mitigating and adapting to risks and changing circumstances is a natural part of doing business. But methods of mitigating and adapting can be quite different in terms of time, cost and observed impacts. The impacts of mitigation activities are more immediate while the benefits of adaptation activities may take many years to take effect. Nowhere is this difference more apparent than in the case of the corporate response to climate change. In the context of climate change, adaptation is the process of changing behaviour in response to actual or expected climate change impacts. Climate change adaptation is now emerging as a critical partner to mitigation, and indeed may even become the primary protection mechanism for future generations. In this unique book, Jason West provides a comprehensive assessment of the management of climate change adaptation in the corporate sector. The book provides a formal overview of the range of approaches available along with a series of practical case studies and examples that can be used by companies and other organisations to identify, assess and manage climate change adaptation. A major focus is on the financial and investment implications of climate change adaptation. West examines how firms can evaluate the investment decisions associated with long-term climate change adaptation measures, including how such investments can be valued and funded, the appropriate accounting treatment of such measures and appropriate risk management and governance practices in relation to such measures. The book also considers the needs and interests of investors and other stakeholders, and considers how they can assess the adequacy and appropriateness of corporate action on climate change. "The Long Hedge" will be essential reading and a key text for risk-practitioners, investors, financiers, scholars and policy makers in the field of climate change